Polisaccharides: Concepts and Classification - Lazo Delgado, Lismet (2019)
The polysaccharides are macromolecules that belong todifferent living beings, whose components aremonosaccharaides joined in a biopolymeric chain.Together with nucleic acids and proteins, polysaccharidesdetermine the functionality and specificity of the species.Polysaccharides have received little promotion despitebeing widely distributed in nature. They are importantmolecules that intervene throughout the body in signaltransduction and cell adhesion. They are also calledcarbohydrates. We can define polysaccharides asbiomolecules formed by the union of a large amount ofmonosaccharides. They are among the carbohydrates, andperform diverse functions, especially of structural andenergy reserves.